Instagram-Driven Customer Journey among Generation Z Café Consumers: An Application of the 5A Model - Mayang Fitri Anggani; Fajar Kusnadi Kusumah Putra; I Gusti Agung Wahyu Adrian; Nenden Dianawati; Edwin Adriansyah (Journal of Business on Hospitality and Tourism, 2025)
This study examines how Instagram shapes Generation Z consumers across the 5A Customer Journey (Aware, Appeal, Ask, Act, Advocate) in an Instagram-driven café context. Adopting a descriptive–diagnostic quantitative design, the study employed purposive (criterion-based) sampling to recruit 100 Generation Z and young adult Instagram users who had been exposed to Baba Goose Café’s Instagram content and had visited the café at least once. Data were collected through a structured Likert-scale questionnaire that operationalized each 5A stage into measurable indicators, and were analyzed using descriptive statistics (frequencies, percentages, and stage-level mean patterns) to compare response distributions across the journey stages. The findings indicate that Instagram performs strongest in the Appeal and Ask stages, supporting emotional attraction and active information search, while awareness is also well supported. However, the Act stage shows comparatively weaker agreement, suggesting potential conversion friction at the Ask-to-Act transition. Advocacy is moderate and more dispersed, indicating heterogeneity in post-experience willingness to recommend. The study contributes stage-level evidence that high visual engagement and inquiry do not automatically translate into behavioral execution, highlighting the need to integrate visual storytelling with conversion-supporting mechanisms to strengthen visitation and sustained advocacy among digitally active young consumers.